Pemodelan Terpadu Pengembangan Energi Terbarukan di Provinsi Gorontalo : Pendekatan Sistem Energi Berkelanjutan - Frandika K. Toiyo; Sudarmanto Hasan; Mohammad Bayu Irawan; Hasim Hasim; Sukirman Rahim (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This study analyzes integrated modeling for renewable energy development in Gorontalo Province, Indonesia, focusing on enhancing sustainable energy systems. The projection for renewable energy usage is expected to reach 23% by 2025. This research identifies various challenges, including dependence on fossil fuels and energy shortages due to inadequate infrastructure. The study employs a quantitative descriptive approach and dynamic system modeling to evaluate the potential of renewable energy sources such as solar, wind, and biomass. The findings indicate that strategic interventions can significantly increase the penetration of renewable energy from 1-2% to 30-40% by 2040, while also reducing carbon emissions and improving energy security. The implications of this research highlight the importance of supportive policies and investments in renewable energy technologies to achieve a sustainable energy transition.